Perkawinan silang antara Keli jantan (Clarias nieuhofii) dan Lele Lokal betina (Clarias batrachus) dengan perbandingan bobot induk yang berbeda - Restu Restu; Peno Nataleo (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2016)
This study aims to determine the weight ratio for crossbreeding between male brood of Clarias nieuhofii and female brood of Clarias batrachus . The observation of the fertilized eggs, shows that: Treatment C, fertilized eggs reached (89%); treatment B (86%), and treatment A (63%). It showed that the ratio of male and female parent was very significant effect on the success of fertilization, as well as on the level of hatching eggs: Treatment of C (38.202%); B (33.72%); and A (15.87%). Survival rate of crossbred seeds had a level of normalcy: 83.335%. The results of this study prove that this crossbreeding is feasible to do. Key words : Clarias nieuhofii, Clarias batrachus, cross breeding, hatching egg.